The gains to bidding firms from merger - Asquith, Paul; Bruner, Robert F.; Mullins, David W. (Journal of Financial Economics, 1983)
This study examines the effect of mergers on the wealth of bidding firms' shareholders. Bidding firms gain significantly during the twenty-one days leading to the announcement of each of their first four merger bids. These results fail to support the capitalization hypothesis that bidders' gains are captured at the beginning of merger programs. Bidders' abnormal returns are positively related to the relative size of the merger partners, and the gains during the announcement period are larger for mergers which are successful. Though the gains are larger prior to 1969, merger bids after 1969 also significantly increase the wealth of bidding firms' shareholders. The results suggest that the inconclusive findings of the earlier studies may be due to methodological deficiencies. The findings of this study are consistent with value-maximizing behavior by the management of bidding firms.